The French staff material from Johann Georg Pasch - Olivier Dupuis (Bern Open Publishing, 2016)
Johann Georg Pasch was a very prolific author who published a large number of books during the third quarter of the seventeenth century. Some of these included physical exercises with a long staff and presented by Pasch himself as coming from France. Among all the known editions, four different versions can be isolated; this offers the possibility to study the filiation of the edition process. This study is combined with a textual criticism of the material, beginning with a comprehensive biography from the author and finishing with the questioning of the French origin.